2015
DOI: 10.1177/2045125315591917
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting use of laxatives in outpatients stabilized on clozapine

Abstract: Constipation is a common and sometimes fatal side effect of clozapine treatment. In this study, we aimed to identify factors associated with clozapine-induced constipation. Data on 202 outpatients stabilized on clozapine treatment were collected. Of these, 71 patients (35%) had a current prescription for laxatives (a proxy for the presence of constipation). Mean clozapine dose was 400.4 mg/day in those prescribed laxatives and 390.1 mg/day in those not prescribed laxatives (p = 0.67), while mean clozapine plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 19 publications
1
25
2
Order By: Relevance
“…The case fatality in ileus has been reported be in the range from 7.3% -27.5% (9-11) versus 3% in agranulocytosis (20, 21) so physicians should be at least as vigilant with regard to constipation and the development of ileus as they are with neutropenia and the possible development of agranulocytosis. The use of laxatives was low in our sample with only 15.6% of patients using laxatives compared to 35% in a UK sample (8). This suggests that laxatives may be underused in Iceland for these patients.…”
Section: Resultscontrasting
confidence: 69%
See 1 more Smart Citation
“…The case fatality in ileus has been reported be in the range from 7.3% -27.5% (9-11) versus 3% in agranulocytosis (20, 21) so physicians should be at least as vigilant with regard to constipation and the development of ileus as they are with neutropenia and the possible development of agranulocytosis. The use of laxatives was low in our sample with only 15.6% of patients using laxatives compared to 35% in a UK sample (8). This suggests that laxatives may be underused in Iceland for these patients.…”
Section: Resultscontrasting
confidence: 69%
“…The risk of constipation has resulted in very high usage of laxatives during clozapine treatment. A UK study on outpatients reported that 35% of outpatients on clozapine used laxatives (8).…”
Section: Introductionmentioning
confidence: 99%
“…Gastrointestinal side effects are common with antipsychotics, particularly clozapine, ranging in severity from mild constipation to fatal bowel obstruction and/or ischemia. Constipation is reported in up to 60% of clozapine-treated patients ( Hayes and Gibler, 1995 ) and up to 50% of those receiving other antipsychotics ( Ozbilen and Adams, 2009 ) and is reflected in the high utilization of laxative in clozapine-treated patients ( Bailey et al, 2015 ). The mechanism is considered to be anticholinergic inhibition of gastrointestinal smooth muscle contraction and peristalsis ( Ozbilen and Adams, 2009 ), but serotonin receptor antagonism likely compounds the problem ( Palmer et al, 2008 ), with serotonin playing a crucial role in regulating gastrointestinal motility ( Crowell, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bailey et al (2015) found clozapine-treated patients using laxatives had on average 29% higher norclozapine concentrations (mean = 0.337 mg/l; SD = 0.19) than those who did not use laxatives (mean = 0.269 mg/l; SD = 0.18); and hypothesized norclozapine's antagonistic properties at the M3 receptor could be promoting gastrointestinal hypomotility. Although norclozapine, like its parent drug, is indeed an M3 antagonist, it is also a potent M1 receptor agonist (Weiner et al, 2004), a molecular property not shared with any other antipsychotic.…”
Section: Discussionmentioning
confidence: 99%